Current status of the human vaginal virome and its relationship with bacterial vaginosis and HIV: A review of the literature. - Herrera-Echeverry, Catalina (2022)
Currently, the human microbiome has been an area of interest in investigation because of its great diversity and dynamism. The rise in the characterization of the microbiome has generated the necessity to subclassify it according to its taxonomy in the different human body regions. The characterization of the virome of the female reproductive tract has become an area of investigation that is growing and that raises different possible mechanisms for diseases that are unknown. In consequence, it is necessary to start identifying the agents involved, their dynamics, and the relation they have with high prevalence diseases like bacterial vaginosis and HIV. Therefore, the purpose of this article was to do a literature review about associations between human vaginal virome, bacterial vaginosis and HIV.